2016
DOI: 10.3390/nu8100642
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Streptococcus thermophilus FP4 and Bifidobacterium breve BR03 Supplementation Attenuates Performance and Range-of-Motion Decrements Following Muscle Damaging Exercise

Abstract: Probiotics have immunomodulatory effects. However, little is known about the potential benefit of probiotics on the inflammation subsequent to strenuous exercise. In a double-blind, randomized, placebo controlled, crossover design separated by a 21-day washout, 15 healthy resistance-trained men ingested an encapsulated probiotic Streptococcus (S.) thermophilus FP4 and Bifidobacterium (B.) breve BR03 at 5 bn live cells (AFU) concentration each, or a placebo, daily for 3 weeks prior to muscle-damaging exercise (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 33 publications
(56 reference statements)
4
90
0
Order By: Relevance
“…The combined effect of probiotic and exercise which lead to improvement in muscular strength and power was also reported in the previous study (Georges et al 2014;Jäger et al 2016).…”
Section: R a F Tsupporting
confidence: 75%
See 1 more Smart Citation
“…The combined effect of probiotic and exercise which lead to improvement in muscular strength and power was also reported in the previous study (Georges et al 2014;Jäger et al 2016).…”
Section: R a F Tsupporting
confidence: 75%
“…The diversity of microbiota composition whether in a multi-strain probiotic or in a single strain probiotic has been proposed as a supplement as it can modulate the anti-inflammatory (i.e., IL-10) and pro-(i.e., IL-6) cytokines in the body to promote a better health over the course of training (Jäger et al 2016;Pedersen et al 2001). The mechanisms of probiotics that actually help to regulate inflammation include (1) indirect effects by boosting the production of short chain fatty acids with anti-inflammatory properties (Vinolo et al 2011), increasing the synthesis of antimicrobial peptides that influence inflammation resolution pathways in the mucosa (Schlee et al 2008), as well as protecting or repairing epithelial barriers (Bermudez-Brito et al 2012;Thomas and Versalovic 2010), and (2) direct effects by binding with the innate immune receptors (Thomas and Versalovic 2010) and triggering pathways that will cause the production of cytokines related with the inflammation (Jeon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise and associated dietary extremes were shown to increase gut microbial diversity in comparison to sedentary people [27]. Some studies have established that probiotic intake can improve low-grade inflammation [28,29] and enhance resistance to URTI in athletes [30,31,32]. In a previous study, Lamprecht and colleagues found that adequate probiotic supplementation composed of six strains consisting of Bifidobacterium bifidum W23, Bifidobacterium lactis W51, Enterococcus faecium W54, Lactobacillus acidophilus W22, Lactobacillus brevis W63, and Lactococcus lactis W58 could improve redox hemostasis and low-grade inflammation in men under sustained exercise stress [29].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of amaranth product would provide large amounts of fibre for the development of gut microbiota, being also a source of vegetable protein. Clinical studies with protein and probiotics (whey + probiotics) showed improved recovery (diminished exerciseinduced muscle damage) in recreationally trained males [63], as well as an improved strength restoration [64], compared to only protein (whey: probably the most widely used protein powder). Further research should be carried to study if this behaviour is mimicked when vegetal proteins (like amaranth's) are used, compared to that of milk (whey).…”
Section: Cardiovascular System Healthmentioning
confidence: 99%